Efficient electrocatalysis for oxygen evolution: W-doped NiFe nanosheets with oxygen vacancies constructed by facile electrodeposition and corrosion - Li, Huixi; Zhang, Chenyang; Xiang, Weijun; Amin, Mohammed A.; Na, Jongbeom; Wang, Shengping; Yu, Jingxian; Yamauchi, Yusuke (Elsevier BV, 2023)
Electrochemical water splitting requires efficient electrocatalysts to accelerate the sluggish kinetics of the oxygen evolution reaction (OER). A promising nanoporous W-doped oxygen vacancy-containing NiFe layered double hydroxides (NiFeW-LDHs) electrocatalyst is directly grown on nickel foam via electrodeposition combined with chemical corrosion. With an appropriate amount of W dopant in NiFe-LDHs, the electronic structures of Ni and Fe are modulated by the changes in local environment, and the oxygen vacancy concentration is further optimized, resulting in abundant OER electrocatalytic active centers on the electrocatalyst surface. Due to the excellent electronic conductivity and three-dimensional nanoporous configuration, the representative NiFeW3-LDHs exhibit remarkable OER electrocatalytic activity with a low overpotential (211 mV at 10 mA cm-2), a small Tafel slope (36.44 mV dec-1), and fine stability (more than 120 h at 10 mA cm-2). The oxygen vacancy effectively modifies the intrinsic electronic structure of NiFe-LDHs, optimizes the adsorption energy of intermediates, and accelerates the OER.